PELAKSANAAN PENDAFTARAN PERSEKUTUAN KOMANDITER (CV), PERSEKUTUAN FIRMA, DAN PERSEKUTUAN PERDATA DI KOTA MEDAN - SITI MARLINA HARAHAP (Journal Law of Deli Sumatera, 2021)
CV is a form of partnership business entity established based on the KUHD by one or several people who entrust money or goods to one or several people who run the company and act as leaders. The implementation of the establishment of a new CV and the implementation of registration of CV names that have been established for a long time before the issuance of Permenkumham No. The results of the discussion of the problems that arise in this study are the application for registration through the minister who carries out legal affairs, information storage regarding CVs, Firms, and Civil Partnerships in Indonesia, especially in the city of Medan, is more sophisticated because it is electronically so that the government in the future is easier to access. Notaries at this time must be able to use electronic media because according to the Regulation of the Minister of Human Rights No. 17 of 2018 concerning Registration of CV, Firms, and Civil Partnerships, there are no exceptions for non-electronic registration because Notaries must be able to carry out their duties electronically.